Sequences and Series: Telescoping Series - Sum

Algebra Level 2

Evaluate

1 4 + 7 + 1 7 + 10 + + 1 397 + 400 . \frac{1}{\sqrt{4}+\sqrt{7}}+\frac{1}{\sqrt{7}+\sqrt{10}}+\cdots+\frac{1}{\sqrt{397}+\sqrt{400}}.

3 3 6 6 397 7 \sqrt{397} - \sqrt7 1 397 + 7 \frac1{\sqrt{397} + \sqrt7}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

S = 1 4 + 7 + 1 7 + 10 + + 1 397 + 400 = 7 4 ( 7 + 4 ) ( 7 4 ) + 10 7 ( 10 + 7 ) ( 10 7 ) + + 400 397 ( 400 + 397 ) ( 400 397 ) = 7 4 7 4 + 10 7 10 7 + 13 10 13 10 + + 400 397 400 397 = 7 4 + 10 7 + 13 10 + + 400 397 3 = 400 4 3 = 20 2 3 = 18 3 = 6 \small \begin{aligned} S & = \frac 1{\sqrt 4 + \sqrt 7} + \frac 1{\sqrt 7 + \sqrt{10}} + \cdots + \frac 1{\sqrt{397}+\sqrt{400}} \\ & = \frac {\sqrt 7 - \sqrt 4}{(\sqrt 7 + \sqrt 4)(\sqrt 7 - \sqrt 4)} + \frac {\sqrt{10} - \sqrt 7}{(\sqrt{10} + \sqrt 7)(\sqrt{10} - \sqrt 7)} + \cdots + \frac {\sqrt{400} - \sqrt{397}}{(\sqrt{400} + \sqrt{397})(\sqrt{400} - \sqrt{397})} \\ & = \frac {\sqrt 7 - \sqrt 4}{7-4} + \frac {\sqrt{10} - \sqrt 7}{10-7} + \frac {\sqrt{13}-\sqrt{10}}{13-10} + \cdots + \frac {\sqrt{400} - \sqrt{397}}{400-397} \\ & = \frac {\cancel{\sqrt 7} - \sqrt 4 + \cancel{\sqrt{10}} - \cancel{\sqrt 7} + \cancel{\sqrt{13}} - \cancel{\sqrt{10}} + \cdots + \sqrt{400} -\cancel{\sqrt{397}}}3 \\ & = \frac {\sqrt{400}-\sqrt 4}3 = \frac {20-2}3 = \frac {18}3 = \boxed 6 \end{aligned}

Brilliant Mathematics Staff
Aug 1, 2020

Rationalizing every term of the given expression results in 1 4 + 7 + 1 7 + 10 + + 1 397 + 400 = 1 7 + 4 × 7 4 7 4 + 1 10 + 7 × 10 7 10 7 + + 1 400 + 397 × 400 397 400 397 = 7 4 3 + 10 7 3 + + 400 397 3 = 400 4 3 = 6. \begin{aligned} &\frac{1}{\sqrt{4}+\sqrt{7}}+\frac{1}{\sqrt{7}+\sqrt{10}}+\cdots+\frac{1}{\sqrt{397}+\sqrt{400}}\\ &=\frac{1}{\sqrt{7}+\sqrt{4}}\times\frac{\sqrt{7}-\sqrt{4}}{\sqrt{7}-\sqrt{4}}+\frac{1}{\sqrt{10}+\sqrt{7}}\times\frac{\sqrt{10}-\sqrt{7}}{\sqrt{10}-\sqrt{7}}+\cdots+\frac{1}{\sqrt{400}+\sqrt{397}}\times\frac{\sqrt{400}-\sqrt{397}}{\sqrt{400}-\sqrt{397}}\\ &=\frac{\sqrt{7}-\sqrt{4}}{3}+\frac{\sqrt{10}-\sqrt{7}}{3}+\cdots+\frac{\sqrt{400}-\sqrt{397}}{3}\\ &=\frac{\sqrt{400}-\sqrt{4}}{3}\\ &=6. \end{aligned}

PLEASE TELL THE SOLUTION USING TELESCOPING SUMS .

Anjali Yadav - 4 months, 4 weeks ago

Log in to reply

Both solutions presented here involved telescoping sum .

Brilliant Mathematics Staff - 4 months, 4 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...